Theoretical Simulation and Experimental Research on Multistage Thermoelectric Cooler - Zhao Ju; Chen Xi (Zhileng xuebao, 2014)
Theoretical analysis of multistage thermoelectric cooler was done in this paper. The cooling temperatures of four different multistage thermoelectric coolers were obtained in three different conditions by ANSYS simulation software. A test bench was conducted to verify the simulation. The simulation results showed that the cooling temperature of thermoelectric cooler was influenced by the distance of the thermoelectric couple, and the distance of thermoelectric couple should be considered in designing the cooler. The test results showed that the optimal operating voltage of the thermoelectric cooler was equal to 12V. The refrigeration temperature was extremely influenced by the external environment. The insulation material had an important impact on the performance of multistage thermoelectric cooler. The test results also showed that the input current and power would decrease with the hot end temperature increasing；The largest temperature difference and cooling temperature would increase with the hot end temperature increasing.